Atención plena : inteligencia emocional - Goleman, Daniel (BookaVivo, 2021)
The benefits of mindfulness include improved performance and creativity, increased self-awareness and personal charisma, as well as greater peace of mind. This book offers in a practical way the steps you must take to develop mindfulness in your professional routine. It also explains the science behind mindfulness and why it works, and warns about the pitfalls it can fall into. This title includes articles by Daniel Goleman, Ellen Langer, Susan David, and Christina Congleton. HBR's Emotional Intelligence series offers a selection of intelligent and essential readings on the human aspects of professional life drawn from articles from the Harvard Business Review. Each book in this series features peer-reviewed research showing how emotions play a role in our work lives. In addition, it offers practical tips for coordinating teams and managing conflictive situations, and stimulating texts that help achieve emotional well-being at work. Inspiring and practical, these books define the soft skills any professional must master.